Chemometric and Computational Strategies for Rational Design of Molecularly Imprinted Polymer - Wu, Xi; Huang, Yan-Ping; Liu, Zhao-Sheng (Current Organic Chemistry, 2016)
Molecularly imprinted polymers (MIPs) are synthetic materials with tailor-made binding sites for a variety of chemical substances. However, the optimization of MIPs formulation is time-consuming and labourintensive since the interactions presenting in the pre-polymerisation mixture are complicated. Therefore, chemometrics, in which mathematical or statistical methods are used to analyze data, has been regarded as a useful tool to the optimization of MIP preparation. This article gave a mini review of the current status of the synthetic strategies in MIPs based on chemometric and computational methods in the past decade. The perspectives in the computation-based optimization for MIP preparation were also discussed.
Keywords: chemometrics